Enforcing Bargains in an Ongoing Marriage - Mary Anne Case (Washington University Journal of Law & Policy, 2011)
This Essay analyzes the presumption against the availability of judicial enforcement for bargains between spouses in an ongoing marriage. It mentions rules on marriage such as one which states that married couples are limited to self-help, extreme step of dissolution and private negotiations. The author discusses the case of McGuire vs. McGuire, which supports the presumption by drawing analogies to the remedies available for relational contracts under the U.S. law.
Keywords: Prenuptial agreements; Marriage; Domestic relations; Law & amp; economics; Divorce mediation; Marital property; Marital separation; Uniform Premarital Agreement Act; Nebraska